Answers

  • Brainly User
2015-09-11T16:22:16+08:00
Let first number be x
      second number be:  x-7
            From x - y =7
                     -y = -x +7
                      y = x - 7 

The square of the sum of two numbers : (x + x - 7)² 

Equation:  
(x + x - 7)² = 289
4x² - 28x + 49 - 289 = 0
4x² - 28x - 240 = 0

Factor the quadratic equation:
4 (x-12) (x+5) = 0

x-12 = 0         x +5 = 0
x = 12           x = -5

The numbers are:
x = 12   and     
x-7  = 12-7 = 5

FINAL ANSWER: 12 and 5

To check:
12-5 = 7
(12 + 5)² = 289
(17)² = 289
289 = 289


0